Effects of Low Doses of Herbicides on Different Endpoints in the Life Cycle of Nontarget Terrestrial Plants. (9th April 2021) - Mathiassen, Solvejg K.; Boutin, Céline; Strandberg, Beate; Carpenter, David; Damgaard, Christian
Abstract: Herbicide drift may cause adverse effects on natural and seminatural plant communities, and it has been debated whether the current ecological risk assessments are adequate to protect nontarget terrestrial plant species. In the present study, 9 nontarget terrestrial plant species with different lifespans (3 annual/6 perennial) belonging to 6 different plant families were exposed to 4 herbicides with different modes of action at the vegetative (6–8 leaf) and reproductive (bud) stages separately. The plant tests were conducted under controlled conditions in 2 greenhouses, 1 located in Denmark and 1 in Canada. For both growth stages, effects were recorded on vegetative (above‐ground biomass 3 wk after treatment) and reproductive endpoints (number and germinability of seeds). In most cases, responses following exposure at the juvenile stage were greater than responses following exposure at the reproductive stage. For the combinations of herbicides and plant species included in the present study, we found that the sensitivities of vegetative and reproductive endpoints were equal, or else vegetative endpoints were more sensitive than reproductive endpoints. We also found that annual species were more sensitive than perennial species. The overall conclusions cover many different response patterns, and it is evident that some effects may not be found in the currently used standard tests. Generally, more pronounced effects were obtained in Denmark compared with Canada, highlighting the fact that even under standardized test conditions and following common guidelines, several uncontrollable factors can still induce variable results. Environ Toxicol Chem 2021;40:1389–1404. © 2021 SETAC